Postmortem Mitragynine Distribution in a Single Drug Fatality Case. Issue 1 (March 2023) - Mata, Dani C.; Chang, Helen H.
A 32-year-old Caucasian male was found unconscious at his sober-living home and pronounced dead after transportation to the emergency room. The decedent had a documented history of substance-use disorder and past suicide attempts, but according to his family, he was sober for the past year. Significant autopsy findings were cardiomegaly, hepatomegaly, congested lungs, cerebral edema, and obesity. The toxicology examination of blood and tissues using liquid chromatography tandem mass spectrometry detected only mitragynine in the central blood (7.5 mg/L), peripheral blood (3.3 mg/L), liver (42.2 mg/kg), and gastric contents (33.1 mg). The qualitative identification of 7-hydroxymitragynine was performed only on the central blood. The pathologist ruled the cause of death acute mitragynine intoxication combined with cardiomegaly with left ventricular hypertrophy, with severe hepatomegaly and obesity listed as other significant conditions. The mode, or manner, of death was determined to be an accidental overdose. To the authors' knowledge, this is the first reported case where mitragynine was the only drug detected. This case study will contribute to the understanding of mitragynine-only death investigation and provide valuable toxicology information for medical examiners and pathologists.